PEMANFAATAN BAHAN AJAR MEMBACA BERBASIS LOKAL UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS IV SEKOLAH DASAR DI PROVINSI BENGKULU - Gumono Gumono (International Conference on Languages and Arts, 2013)
The aim of this action research is improving students' reading comprehension skills, using local conditions based teaching materials. The comprehension in this research means understanding of the main ideas, facts, opinions, comparisons, and the opposition. Types of data in this research used is the learning process data and student learning outcomes data. Data collected by observation techniques, the study documents, and test. Key instrument of this research is the researcher himself, by making use of supporting instruments in the form of guidelines for observation, document analysis, and test items. Validity test of the data carried by persistent observation, triangulation, and peer review. Data were analyzed using qualitative data analysis techniques of interactive models and simple quantitative analysis. Action research conducted in two cycles. The results of this research is reading instruction using  local conditions based reading materialscan: (a) (1) increasing students' schemata about reading, (2) improving the readiness of self and mental students to understand the content of reading, and (3) increasing the curiosity to the contents of reaing materials; (b) can lead students to determine the purpose of reading; (c). improving student proficiency suggests that information gained from reading and discussion group; and (d) improving students’ speaking skills through brainstorming and improving students’ writing skills through written information obtained from literature. Kata Kunci: pembelajaran, keterampilan membaca, bahan ajar berbasis lokal, sekolah dasar